IMPROVING UNDER-RESOURCED SECONDARY SCHOOL TEACHERS’ LITERACY INSTRUCTION: AN INTERVENTIONAL ETHNOGRAPHIC STUDY - Wirza, Yanty; Gunawan, Wawan; Setyaningsih, Anita T; Ramdani, Sarah A; Hanipah, Hanipah; Aufa, Fellia L.; Edelweis, Sherly L.B. (International Journal of Education, 2023)
The study is a part of the government-sponsored literacy program to improve the Indonesian secondary students’ literacy performance. Particularly, this study focuses on the examination of the program as the attempt to improve the secondary teachers’ literacy instruction at the under-resourced schools. The program implemented in the Bahasa Indonesia subject by employing Reading to Learn pedagogy (Rose, 2016) in teaching the explanatory text. Using an interventional ethnographic study design, which involves three main phases i.e. Reading to Learn pedagogy workshop, the R2L implementation with mentoring, and evaluation, the current study investigates the experience of two female eighth graders’ contract-based teachers, in their early thirties, at two under-resourced secondary schools in, Bandung, West Java, Indonesia. The data collected in this three-month study were observation, interviews with the teachers, principal, and students, recorded teaching sessions, recorded reflections sessions, and lesson plans and teaching materials. The findings of the study reveal that the teachers’ literacy instruction in utilizing stages in the R2L pedagogy indicated significant improvement from their previous practice. The intensive mentoring provided during the workshop and school implementation of the R2L implementation have equipped the teachers with more solid pedagogical foundation in internalizing and implementing the R2L pedagogy. In addition, the program has promoted the teachers’ professional development and assisted the school to gain larger access to literacy pedagogy for better literacy participation.